APLIKASI BERBAGAI KONSENTRASI GA3 DAN PUPUK NPK TERHADAP PERTUMBUHAN TANAMAN ANGGREK BULAN (PHALAENOPSIS AMABILIS L.) - istiqoma Rusdiana Rahayu (AGRONISMA, 2020)
In the vegetative phase, orchids grow very slowly. Orchid plants need a higher element N (nitrogen) which aims to form organs in the vegetative phase (leaves, roots, and stems), besides the orchid plants require ZPT GA3 which functions for cell division. The research was conducted at the Agriculture Faculty Screenhouse, Malang Islamic University, Lowokwaru District, Malang City. The study was conducted in October 2019 until February 2020. The factorial experimental design was prepared using a Randomized Block Design (RBD) consisting of 2 treatment factors. Factor 1: Concentration of growth regulator GA3, consists of 3 levels: G0: GA3 concentration 0 ppm, G2: GA3 concentration 2 ppm, G4: GA3 concentration 4 ppm. Factor 2: NPKfertilizer concentration, consisting of 3 levels: P0: NPKFertilizer 0 g/ l, P1: NPKFertilizer 1 g/ l, P3: NPKFertilizer 3 g/ l. the tools needed are flexible cup, camera, stationery, bucket, spectrophotometer, etc. The materials used were orchid seedlings aged 6 months, charcoal, kadaka roots, cocofiber, moss, NPKgrowmore, GA3. Observed//variables,,included./plant height, number of leaves,,.leaf area, total chlorophyll. Data obtained in the analysis using analysis of variance to determine the effect between treatments. If there is an influence between treatments continued using the Least Significant Difference test (LSD) level of 5%. The results showed that in general the application of various concentrations of GA3 and NPKfertilizer showed a significant effect on the growth of orchid plants. At plant height the results of analysis of variance showed that in general there were no real interactions at each age of observation. Orchid plants have the best number of leaves in the treatment P1 (concentration of 1 gL-1). In the leaf area there was a significant interaction at the age of 45 hsr observed in the G4P0 treatment (GA3 4 ppm and NPK fertilizer 0 g L-1) but, not significantly different from the G0P3 treatment (GA3 0 ppm and NPK fertilizer 3 g L-1). In the stem diameter there was a significant interaction at the age of 75 hsr observed in the treatment of G4P1 (GA3 4 ppm and NPK fertilizer 1 g L-1), but not significantly different from G0P1 (GA3 0 ppm and NPK fertilizer 1 g L-1) and G0P3 (GA3 0 ppm and NPK fertilizer 3 g L-1). In the chlorophyll content obtained the highest value in the treatment of G4P3 (GA3 4 ppm and NPK fertilizer 3 g L-1), but not significantly different from the treatment of G2P3 (GA3 2 ppm and NPK fertilizer 3 g L-1). Based on these results the use of GA3 andNPK fertilizer on the growth of orchids gives tangible results, the function of GA3 which is aimed at cell division, while theNPK fertilizer which functions to stimulate vegetative growth of the whole plant (leaf area, number of leaves, roots, and stems).